The Role of the Scientific Council “Cybernetics” of the USSR Academy of Sciences/the Russian Academy of Sciences in the Development of National Cybernetics and Computer Technology - Amirdjanov, G. P.; Gurevich, I. B.; Kostyuk, F. V.; Kulberg, N. S.; Rudchenko, T. A.; Semenov, A. L.; Sotnikov, A. N.; Trusova, Yu. O.; Uvarov, A. Yu; Vardanyan, V. A.; Yakovleva, T. V.; Yashina, V. V.; et al. (Pattern recognition and image analysis, 2023)
The review presents the history of the creation and work of the Scientific Council “Cybernetics” (SCC)—the center for development of cybernetics in the USSR and Russia. The Council’s activity is covered as a structure that coordinates scientific and technical activity in cybernetics in the country via a system of sections: about 16 public and professional bodies involving thousands of specialists. Brief information about the sections is given. The chronology of development of the SCC is discussed, in particular, information about its chairmen, starting with the renowned organizer of research and development, Academician and Admiral Axel Ivanovich Berg and the following academicians: B.N. Petrov, O.M. Belotserkovsky, A.P. Ershov, E.P. Velikhov, B.V. Bunkin, and Yu.I. Zhuravlev. The SCC’s publishing activity is briefly reviewed. The second function, built into the SCC from its onset, is as a research institute conducting its own research on the most pressing scientific problems insufficiently covered by existing structures. Several main areas of research by the SCC itself and its successor, the Axel Berg Institute of Cybernetics and Educational Computing of the Federal Research Center “Computer Science and Control” of the RAS: coding and transmission of information, economic cybernetics, aircraft control, supercomputers, digital technologies in education, mathematical logic and the theory of algorithms, pattern recognition and image analysis, mathematical methods of image analysis, theoretical physics, biomedical cybernetics, and ultrasound imaging. Another function of the SCC is considered: as an incubator of new academic industrially oriented structures and the fate of one of them—the Institute of Cybernetics Problems—is traced.